The Long Noncoding RNA Gm9866/Nuclear Factor-κB Axis Promotes Macrophage Polarization - Xiaomin Liao; Xianxian Ruan; Xiubing Chen; Biaolin Zheng; Xianbin Wu; Zhejun Deng; Zhe Yang; Feng Wang; Shanyu Qin; Haixing Jiang (Mediators of Inflammation)
Macrophages are a type of immune cells with high levels of plasticity and heterogeneity. They can polarize into M1 or M2 functional phenotypes. These two phenotypes exhibit a dynamic balance during polarization-related diseases and play opposing roles. Long noncoding RNAs (lncRNAs) play an important role in biological processes such as cell proliferation, death, and differentiation; however, how long noncoding RNAs affect the cellular functionality of macrophages remains to be studied. Long noncoding RNA Gm9866 was found to be closely related to macrophage polarization through bioinformatics analysis. In this study, by conducting real-time polymerase chain reaction analysis, it was observed that long noncoding RNA Gm9866 expression significantly increased after treatment with interleukin-4 but significantly decreased after treatment with lipopolysaccharide. Fluorescence in situ hybridization revealed that long noncoding RNA Gm9866 was expressed mainly in the nucleus. Real-time polymerase chain reaction analysis showed that overexpression of long noncoding RNA Gm9866 in RAW264.7 cells further promoted the expression of M2 markers MRC1 (macrophage mannose receptor 1) and MRC2 (macrophage mannose receptor 2). Western blotting analysis demonstrated inhibition of nuclear factor-κB (NF-κB) expression. EdU (5-ethynyl-2′-deoxyuridine) and TUNEL (TdT-mediated dUTP nick-end labeling) staining assays revealed that overexpression of long noncoding RNA Gm9866 promoted cell proliferation and inhibited apoptosis. These findings thus indicated that long noncoding RNA Gm9866 promoted macrophage polarization and inhibited the nuclear factor-κB signaling pathway. Thus, long noncoding RNA Gm9866 may serve as a potential diagnostic and therapeutic target for polarization-related diseases such as infectious diseases, inflammatory diseases, liver fibrosis, and tumors.